Looking in the Side-View Mirror: Assessing the Current and Future State of the Solar Energy Industry as it Reaches the Mainstream - Palumbo, Brian (Columbia Journal of Environmental Law, 2019)
The popularity of solar energy has risen as its cost has rapidly decreased since 2005. A Deutsche Bank projection claims that the cost of solar energy will reach grid parity by 2016, and an International Energy Agency report asserts that by 2050, solar energy could be a viable source of electricity worldwide. On its face, these projections depict a bright future for solar energy and society. Yet solar energy’s presence as an alternative form of energy might be more vulnerable than forecasts depict. With the upcoming expiration of valued government incentives and pushback from energy competitors, solar energy will not run untouched to the end-zone. In other words, solar energy approaches a critical juncture where its deficiencies might come to the forefront. To view these vulnerabilities, a qualitative investigation of solar energy is required. Solar energy is growing at a remarkable rate, yet there are factors intrinsic to the industry that have not yet influenced its growth into adolescence. One must analyze current solar energy issues along with the industry’s unique characteristics to properly assess the situation from a complete perspective and to observe its possible exposure to an array of complications. Lawmakers, from all levels of government, must then acknowledge and act on these findings to prudently regulate the solar industry.